“Human side” of ISO Standards Implementation : An Exploratory Qualitative Analysis Study of the Inner, Surface, and Outer Effect of ISO Implementation Process on Employees - Dmitrieva, Alina (2013)
Inner, Surface and Outer constitutes ISO. Inner part refers to I in ISO – it describes the way people feel, their emotions and feelings. Surface manifestation refers to S in ISO – the way people behave and act. Finally, Outer refers to O in ISO – the spirit, intangible psychological contract that connects people`s feelings to their behavior. Thus, inner, surface and outer are the constituents of a system, parts of a whole. As parts can not be excluded from the system without loss, so one of the elements of ISO implementation process can not be eliminated without damaging any other part. This study will be based on qualitative analysis of inner, surface and outer effect of ISO implementation process on employees in the context of organization culture and psychological contract perspectives; the focus will be given to a “human side” of ISO implementation processes.